2019
DOI: 10.1016/j.rasd.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving autism screening in French-speaking countries: Validation of the Autism Discriminative Tool, a teacher-rated questionnaire for clinicians’ use

Abstract: Background: Autism screening remains a major challenge in most French-speaking countries. Two main issues contribute to this problematic situation: unavailability of tests in French and psychometric/ methodological weaknesses of existing instruments. These shortfalls result in late and inadequate referrals to autism specialist clinics, jeopardising both children's diagnosis and prognosis. This article describes the validation of the Autism Discriminative Tool (ADT), a teacher-rated level-two screener for child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Moreover, previous studies have shown that false knowledge and beliefs about autism can lead to delays in diagnosis and access to services (Harrison et al, 2017), which is frequent in France ( Stratégie nationale pour l'Autisme au sein des troubles du neurodéveloppement , 2018). As teachers are key players in identifying the early signs of autism, it is crucial to look at how to improve their knowledge and perceptions of autism (Carlier et al, 2019; Schanding et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that false knowledge and beliefs about autism can lead to delays in diagnosis and access to services (Harrison et al, 2017), which is frequent in France ( Stratégie nationale pour l'Autisme au sein des troubles du neurodéveloppement , 2018). As teachers are key players in identifying the early signs of autism, it is crucial to look at how to improve their knowledge and perceptions of autism (Carlier et al, 2019; Schanding et al, 2012).…”
Section: Introductionmentioning
confidence: 99%